2020
DOI: 10.21203/rs.3.rs-25857/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global economic footprint of the COVID-19 pandemic

Abstract: Countries around the world have sought to stop the spread of the 2019 novel coronavirus (COVID-19) by severely restricting travel and in-person commercial activities. Here, we analyse the economic footprint of such “lockdowns” using detailed datasets of global supply chains and a set of pandemic scenarios. We find that COVID-related economic losses are largely dependent on the number of countries imposing lockdowns, and that losses are more sensitive to the duration of a lockdown that its strictness—suggesting… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 33 publications
(41 reference statements)
2
46
2
Order By: Relevance
“…However, there is now growing evidence of second-round effects, with unemployment growing in sectors that are not directly impacted by the containment, but by supply chain effects (e.g., affected firms reducing demand for other firms) or the aggregate drop in demand. To estimate these effects, a next step is to connect the household model presented here to an Input-Output model, such as the one used in (Guan et al 2020) to look at how COVID-19 affects global supply chains, or a Computable General Equilibrium (CGE) model. Alternatively, using payroll data such as the Bureau of Labor Statistics (BLS) Current Employment Statistics (CES) or other employment data can be used as an input to the model for a better representation of labor income loss by industry sector.…”
Section: Assumptions Limitations and Future Workmentioning
confidence: 99%
“…However, there is now growing evidence of second-round effects, with unemployment growing in sectors that are not directly impacted by the containment, but by supply chain effects (e.g., affected firms reducing demand for other firms) or the aggregate drop in demand. To estimate these effects, a next step is to connect the household model presented here to an Input-Output model, such as the one used in (Guan et al 2020) to look at how COVID-19 affects global supply chains, or a Computable General Equilibrium (CGE) model. Alternatively, using payroll data such as the Bureau of Labor Statistics (BLS) Current Employment Statistics (CES) or other employment data can be used as an input to the model for a better representation of labor income loss by industry sector.…”
Section: Assumptions Limitations and Future Workmentioning
confidence: 99%
“…By amplifying underlying inequities in the distribution of resources, the socioeconomic disruption caused by the response to COVID-19 will almost certainly have negative long-term impacts on human health and well-being. In particular, the economic shock is likely to increase the extent and severity of global poverty 50 , both from direct impacts on health, employment and incomes and through disruptions of supply chains and global trade 51 . The severe impacts on poverty rates and food security that are already emerging 50 are indicative of these disruptions and are a sign of how tightly many of the world's poorest households are now interwoven into the global economy.…”
Section: Path Ii: Poverty Globalization Food and Biodiversitymentioning
confidence: 99%
“…2a) and extends across the seasonal transition from Northern Hemisphere winter to summer (and potentially beyond). Further, the scale of economic impacts suggest the possibility of sustained recession -or even depression -following the cessation of large-scale sheltering 51,66 . An extended period of substantially reduced economic activity would produce a trajectory of Earth System forcing that remains different from the pre-COVID-19 forcing, well after the COVID-19 restrictions are removed.…”
Section: A New View To Spatial and Temporal Dynamics Of Earth System mentioning
confidence: 99%
“…Third, although the econometric analysis of /citeBarrot2016, Boehm2019, Carvalho2016, Kashiwagi2018 quantitatively confirms propagation through supply chains, their analysis cannot estimate the total effect of a shock that can be obtained from the framework of Inoue and Todo [7]. Finally, the studies estimating the effect of COVID-19 rely on either a macroeconomic econometric model at the country level [14] or a general equilibrium model assuming international and inter-sectoral IO linkages [6,[15][16][17] and thus do not incorporate complex inter-firm linkages. As a result, the estimates of the previous studies may be largely undervalued, as suggested by the findings of Inoue and Todo [7].…”
Section: Introductionmentioning
confidence: 99%